STUDY ON ENERGY ABSORPTION CHARACTERISTICS OF CIRCULAR TUBE WITH RECTANGULAR GROOVE BASED ON REGRESSION ANALYSIS - LEI Cheng; LI FuSheng; MIAO DeXiang; ZHU Tao (Jixie qiangdu)
In order to study the energy absorption characteristies of circular tubes with rectangular groove, a method based on regression analysis of fitting the relationship between structural parameters and energy absorption characteristics was proposed. Firstly, Cowper-Symonds constitutive model of 6005A-T6 was established, which was used as input to verify the accuracy of the simulation model of circular tubes. Secondly, an orthogonal experiment on energy absorption characteristies and structural parameters was designed, and a nonlinear calculation model between the two was established. Then. the mult tiple linear anc nonlinear regression analysis methods were used to solve the calculation model parameters, and the empirical formulas of peak force and energy absorption were obtained by comparing the two fitting results. By comparing the calculated value of the empirical formula with the finite element numerical value, the empiricalformula has higher accuracy within the research range, and the error is within 8%. Finally, the energy absorption performance index was introduced and the structure of the circular tube was optimized by genetic algorithm. The optimization results show that when the diameter and the groove end distance are the smallest. the wall ess and the groove width are the largest, and the groove depth is the shallowest, the circular tube has the best energy absorption performance in the range of research.